2002
DOI: 10.1038/oby.2002.174
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Depletion and Apoptosis Induced by Trans‐10, Cis‐12 Conjugated Linoleic Acid in Mice*

Abstract: depletion and apoptosis induced by trans-10, cis-12 conjugated linoleic acid in mice. Obes Res. 2002;10:1284 -1290. Objective: To compare the effectiveness of a conjugated linoleic acid (CLA) isomer mixture (mCLA) with each main isomer [trans-10,cis-12 CLA (CLA10,12) and cis-9,trans-11 CLA (CLA9,11)] in causing body lipid loss and adipose tissue apoptosis. Research Methods and Procedures: Mice selected over 16 generations for high (MH) or low (ML) energy expenditure and a control group (MC) were fed diets cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 26 publications
(32 reference statements)
8
71
2
Order By: Relevance
“…Further, recent studies substantiate the concept that adipocyte deletion by apoptosis is a significant contributor to the regulation of adipose tissue mass and its loss during weight reduction (Della-Fera et al 2001, Hargrave et al 2002, Fischer-Posovszky et al 2004, Kim et al 2004, Sun & Zemel 2004. Our retroperitoneal adipose tissue cell density data clearly showed that chronic vitamin A challenging through diet had no impact on cell size.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Further, recent studies substantiate the concept that adipocyte deletion by apoptosis is a significant contributor to the regulation of adipose tissue mass and its loss during weight reduction (Della-Fera et al 2001, Hargrave et al 2002, Fischer-Posovszky et al 2004, Kim et al 2004, Sun & Zemel 2004. Our retroperitoneal adipose tissue cell density data clearly showed that chronic vitamin A challenging through diet had no impact on cell size.…”
Section: Discussionsupporting
confidence: 65%
“…Apoptosis has been described both in WAT and brown adipose tissue (BAT) (Prins et al 1994). Several studies have demonstrated in vitro and in vivo adipocyte apoptosis under various conditions such as growth factor deprivation, dietary conjugated linoleic acid supplementation and streptozotocin administration , Loftus et al 1998, Miner et al 2001, Hargrave et al 2002. Even in patients with malignancy-associated weight loss, apoptosis is detected in abdominal, subcutaneous and omental fat (Prins et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…phytochemicals, such as esculetin, resveratrol, quercetin, genistein, capsaicin, and conjugated linoleic acids induced apoptosis of maturing 3T3-L1 preadipocytes through suppression of ERK1/2 phosphorylation, activation of the mitochondrial pathway, AMPK activation, or anti-oxidant activity [51][52][53][54][55]. Sirtuin 1 is another target molecule for anti-obesity treatment.…”
Section: Adipogenesis Down Regulationmentioning
confidence: 99%
“…It is well established that cis 9,trans11 (c 9t11)-CLA and trans 10,cis 12 (t10c12-CLA) have unique effects on lipid metabolism (12), and it is the t10c12-CLA isomer that is mainly associated with decreases in body fat in experimental rodent models (13)(14)(15)(16) as well as in some but not all human studies (17)(18)(19), independently of energy intake (20).…”
mentioning
confidence: 99%